Transforming Digital Pedagogy in Primary School Teacher Education (PGSD) to Enhance Learning Quality in the Post-Pandemic Era - Riza Adrian Ibrahim; Alim Jaizul; Yasir Salih (Research Collaboration Community (Rescollacom), 2026)
The transformation of digital pedagogy has become a crucial aspect of improving the quality of education, particularly in the post-pandemic era. This study aims to analyze the role of digital pedagogy in Primary School Teacher Education (PGSD), focusing on its potential to enhance teaching effectiveness, student engagement, and learning outcomes. The research employs a qualitative approach through a systematic literature review of scholarly articles and educational reports published between 2021 and 2026. The findings reveal that digital pedagogy supports interactive learning environments, promotes student-centered approaches, and strengthens teachers’ instructional competencies. However, challenges such as limited digital infrastructure, insufficient teacher readiness, and gaps in digital literacy persist. Furthermore, the shift toward hybrid and technology-based learning requires continuous adaptation from both educators and institutions. Therefore, integrating digital pedagogy into PGSD curricula is essential to prepare future teachers who are innovative, adaptive, and technologically competent. The study concludes that strategic policy support, infrastructure development, and ongoing professional training are key factors in optimizing digital pedagogy implementation in primary education.